Controlled release of dexamethasone from fibrin sealant for intratympanic administration in inner ear therapy - Jing Zou (Journal of Otology, 2024)
The aim of the present work was to show the sustainability of fibrin sealant in releasing dexamethasone and adjust the protocol for clinical application of the novel method in the treatment of Meniere's disease (MD) and sudden sensorineural hearing loss (SSHL). Gelation occurred shortly after mixing dexamethasone-containing fibrinogen with thrombin. Dexamethasone was constantly released for at least 16 d at a stable level after 7 d in protocol 1 (low-dose), while it was robustly released within 4 d and slowed afterward until 10 d in protocol 2 (high-dose). There were significant differences among the time points in Protocol 2 (p < 0.01, ANOVA), and the exponential model with the formula y = 15.299 * e−0.483 *t fits the association. The estimated concentration of dexamethasone released on 7 d in protocol 2 was slightly lower than that observed in protocol 1. The fibrin sealant is capable of constantly releasing dexamethasone with adjustable dynamics. Targeted and minimally invasive administration of the material can be achieved in the clinic by sequential injections of the fluids using a soft-tipped catheter.